2x-5+x+20+3x-10=

Simple and best practice solution for 2x-5+x+20+3x-10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5+x+20+3x-10= equation:


Simplifying
2x + -5 + x + 20 + 3x + -10 = 0

Reorder the terms:
-5 + 20 + -10 + 2x + x + 3x = 0

Combine like terms: -5 + 20 = 15
15 + -10 + 2x + x + 3x = 0

Combine like terms: 15 + -10 = 5
5 + 2x + x + 3x = 0

Combine like terms: 2x + x = 3x
5 + 3x + 3x = 0

Combine like terms: 3x + 3x = 6x
5 + 6x = 0

Solving
5 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 6x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 6x = 0 + -5
6x = 0 + -5

Combine like terms: 0 + -5 = -5
6x = -5

Divide each side by '6'.
x = -0.8333333333

Simplifying
x = -0.8333333333

See similar equations:

| 9p-7=-3p+7 | | 9p-7=3p+7 | | 4x^3-24x^2-16=0 | | 32u=-7 | | 5x+23(x-4)=272 | | .12x+0.1(5000-x)=560 | | -7v=14 | | 4x^2+8x=y | | X-6x=0 | | 17x+17+102z= | | 5(90-7x)=x-26 | | 9p+13=4p-2 | | (x)(x^5)(x^4)= | | 17(x+1+6z)= | | -a=-34 | | 2+z=7 | | 1x-3=9x+3 | | 3x+10=2x+12 | | -2s=-72 | | -8a-6a= | | 13-s=50 | | y=3x^2+2x-5 | | 19+z=80 | | 0.05x=1760 | | 77-3x=15x+17 | | b-2x=(-6)-2(6) | | (6x+1)+x=4x+19 | | 4x+9=-107-7x | | (2-a)(2-a)-4=0 | | x+.23=24.60 | | 3-2y=(3y-2)-5y | | 7q+11=102 |

Equations solver categories